Rinsing Chronic Wounds with a Nitric Oxide Containing Solution – A Safe Treatment Approach to Support Wound Healing - Meyer, Thorsten U. (Current Bioactive Compounds, 2020)
Background: Nitric oxide (NO) is known for decades to play a crucial role in many physiological processes: this includes acting as an anti-microbial mediator/agent, vasodilator, inhibitor of platelet aggregation, immune modulator, and tissue regeneration via regulation of epidermal cell migration, collagen deposition and cytokine/chemokine microenvironment, making it a key player in wound healing. Methods: In order to demonstrate the therapeutic benefits as well as the safety of a NO wound irrigation solution, a broad literature review summarizing efficacy and safety data was conducted. Results: Beneficial effects on wound healing have been demonstrated in several non-clinical and clinical studies. The combination of NO and wound rinsing seems to be a promising approach in terms of improved wound healing of chronic wounds. Conclusion: Based on the results, no safety concerns are expected for a daily 15 minutes use of a NOgenerating rinsing solution system for wound irrigation of diabetic foot ulcers in adults.
Keywords: chronic wound